2021
DOI: 10.1016/j.heliyon.2021.e07580
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids enriched ethanol extracts of aerial roots of Ceriops decandra (Griff.) and Ceriops tagal (Perr.) promote diuresis in mice

Abstract: Introduction: Ceriops decandra (CD) and Ceriops tagal (CT) are two traditionally used mangrove plants widely distributed along the coastal areas of South Asia, Africa, South Pacific. In this study, we evaluated the diuretic potential of aerial roots of CD, CT and assessed the effectiveness of the plants' terpenoids enriched bioactive constituents against human carbonic anhydrase (hCA) enzyme through molecular docking. Materials and methods: Firstly, the acute toxicity of CD and CT was evaluated in mice. In viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Therefore, βamyrin could also play a role in diuretic activity. Our literature findings also revealed that terpenoid-enriched plant extracts promote diuresis, which supports this result 74 .…”
supporting
confidence: 87%
“…Therefore, βamyrin could also play a role in diuretic activity. Our literature findings also revealed that terpenoid-enriched plant extracts promote diuresis, which supports this result 74 .…”
supporting
confidence: 87%
“…TTC was quantified by the Biswajit Biswas method, and TPC was determined using the Folin–Ciocalteu reagent. , TPC and TTC were presented as milligrams of gallic acid equivalent per gram of dried weight (mg GAE/g dw) and milligrams of ursolic acid per gram of dried weight (mg UA/g dw), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The method of determination of tannins content was prescribed by (Myo & Khat‐udomkiri, 2022). Terpenoid was measured referring to the method of determination of terpenoid in aerial roots of Ceriops decandra and Ceriops tagal (Biswas et al ., 2021). The results of TFC, TTAC, and TTC were expressed as milligram rutin, catechin, and ursolic acid equivalent per gram of dry basis (mg RE/g db, mg CE/g db, and mg UE/g db), respectively.…”
Section: Methodsmentioning
confidence: 99%